The Strengths and Weaknesses of the Singing Method in Improving the Language Skills of Teuku Syam Aceh Besar Kindergarten - Kartini Kartini; Wahyu Khafidah; Nadia Maulizhar; Kaida Rahmawati; Magfirah Magfirah; Rajiatul Mawaddah; Putri Mauliza; Putri Amalia; Hilmayada Hilmayada (Universitas Serambi Mekkah, 2022)
This research used qualitative research methods togather information using observation, interviews and documentation. The results of the study regarding the value of the initial description of children's language development in the developing category according to expectations (BSH) 16.7% and developing very well (BSB) listening to words 10%. The ability to pronounce 30% of children's language skills at Teuku Syam Aceh Besar Kindergarten with an average completeness score of 78.9% of children's learning outcomes and is in a very well-developed category. Keywords: Singing, Young Learners, and Language Skills